2018
DOI: 10.1002/fsn3.577
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence and production of tenuazonic acid in wine grapes in Argentina

Abstract: A survey was carried out to determine natural occurrence of tenuazonic acid (TA) in healthy and rotten wine grapes samples from different varieties (n = 37) collected during 2016 vintage in the region of DOC San Rafael (Argentina). In addition, inoculation experiments with three Alternaria alternata strains in wine grapes were done to elucidate TA production and its major influencing factors. The 16.2% (6/37) of total wine grape samples showed TA contamination with 4% (1/25) of incidence in healthy samples (77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous studies about the requirements of water and temperature for A. alternata growth have revealed that this fungus requires a minimum of 0.84-0.88 a W , and optimal growth has been observe at 0.98 to 1.0 a W at 25 • C [26][27][28][29]40,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies about the requirements of water and temperature for A. alternata growth have revealed that this fungus requires a minimum of 0.84-0.88 a W , and optimal growth has been observe at 0.98 to 1.0 a W at 25 • C [26][27][28][29]40,41].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies in the literature dealing with the effect of a W and temperature on mycotoxin production by A. alternata strains on natural substrates or on media-based natural substrates [26][27][28][29]41,43], but only a few have been performed with A. arborescens [40,44]. It is important to remark that none of them have been performed on chickpea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TA could cause serious problems acting as pro-carcinogen in esophageal mucosa. Consequently, it is crucial to measure the accepted levels of TA toxins in grape-derived products (Prendes et al, 2018). Previously, TA was reported at high levels (139.2-115.5 µg/L) in 42.5% of Iranian grape juice (Safavizadeh et al, 2020).…”
Section: Alternaria Toxinsmentioning
confidence: 99%
“…2016; Prendes et al . 2018b). Additionally, there are numerous studies reporting the natural occurrence of AOH, AME and TA on grape juices and wine (Scott et al .…”
Section: Introductionmentioning
confidence: 99%